Study on Preparation Method of Terminal Blend Rubberized Asphalt Binder - Xie, Juan; Zhang, Yongning; Yang, Yueming (Frontiers in Materials, 2020)
Terminal Blend rubberized asphalt binder is generally prepared under high temperature conditions. Unlike asphalt plants that produce asphalt in sealed asphalt tanks, the process of laboratory interaction of asphalt and crumb rubber is mostly in contact with air, which can easily cause asphalt aging. To alleviate this phenomenon, TB-B and TB-C asphalt were prepared using crumb rubber in a nitrogen environment and soluble crumb rubber in an atmospheric environment, respectively.As a comparison group, TB-A asphalt was prepared using crumb rubber under atmospheric environment. A practical method for preparing TB asphalt was explored by changing the amount of crumb rubber and the interaction temperature. Their rheological characteristics were measured by dynamic mechanical methods using dynamic shear rheometer (DSR) and binding beam rheometer (BBR). It was found that under high interaction conditions, the crumb rubber in TB-A asphalt undergoes desulfurization and degradation reactions, which caused the hinge structure in the asphalt to be damaged and the high-temperature performance decreased. But the aliphatic compounds generated by the degradation of crumb rubber are beneficial to improve the low temperature performance of asphalt. Through polymer isolation experiments, it was found that the degradation of crumb rubber caused TB-A and TB-B asphalt to form a homogeneous system. While the soluble crumb rubber in TB-C asphalt was mainly swelling reaction, so the larger the amount of soluble crumb rubber, the more severe the segregation. Besides, the aging degree of three TB asphalts was studied by using viscosity experiments, thermal analysis and Fourier transform infrared (FT-IR) spectroscopy. The results show that compared with TB-A asphalt, the aging degree of TB-B and TB-C asphalt is greatly reduced. Therefore, both preparation methods effectively alleviate the aging phenomenon in the laboratory preparation of TB asphalt.